PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP KETERAMPILAN KOMUNIKASI DAN PERFORMA SISWA DI SMK NEGERI 1 KOTA JAMBI - Jeni Rotua Lastiur Simbolon; Erisa Kurniati; Linardo Pratama (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study aims to analyze and explain the effect of teachers’ pedagogical competence on students’ communication skills and performance at SMK Negeri 1 Jambi City. The study was motivated by the importance of communication skills and student performance as essential non-technical competencies required in the workplace, particularly in vocational education. However, students’ communication skills and performance are still not optimal, highlighting the need for effective pedagogical competence among teachers. This study employed a quantitative approach using an explanatory research method. The population consisted of 1,846 students, and a sample of 187 respondents was selected through simple random sampling. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with SmartPLS 4 software. The results indicate that teachers’ pedagogical competence has a positive and significant effect on students’ communication skills (p-value = 0.000 < 0.05; T-statistic = 12.430 > 1.96) and student performance (p-value = 0.000 < 0.05; T-statistic = 6.483 > 1.96). Teachers’ pedagogical competence also contributes to communication skills (R² = 0.509) and student performance (R² = 0.338). These findings emphasize that improving teachers’ pedagogical competence plays an important role in enhancing students’ communication skills, performance, and readiness to enter the workforce.